2017
DOI: 10.1016/j.neuron.2016.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial Prefrontal Cortex Encodes a Latent Estimate of Cumulative Reward

Abstract: Humans and other animals accumulate resources, or wealth, by making successive risky decisions. If and how risk attitudes vary with wealth remains an open question. Here humans accumulated reward by accepting or rejecting successive monetary gambles within arbitrarily defined temporal contexts. Risk preferences changed substantially toward risk aversion as reward accumulated within a context, and blood oxygen level dependent (BOLD) signals in the ventromedial prefrontal cortex (PFC) tracked the latent growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(89 citation statements)
references
References 71 publications
12
77
0
Order By: Relevance
“…These findings build on our previous work implicating the human vmPFC in coding an internal, unsignalled representation of cumulative assets in a way that maximises a specific goal (maintaining net positive aggregate reward), over and above any momentary hedonic value that arises from choices 23 . However, the current work additionally implies why the brain keeps track of cumulative assets – because this allows any imbalance among internal needs to be redressed by future choices.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings build on our previous work implicating the human vmPFC in coding an internal, unsignalled representation of cumulative assets in a way that maximises a specific goal (maintaining net positive aggregate reward), over and above any momentary hedonic value that arises from choices 23 . However, the current work additionally implies why the brain keeps track of cumulative assets – because this allows any imbalance among internal needs to be redressed by future choices.…”
Section: Discussionsupporting
confidence: 76%
“…bandit or food choice tasks) that involve maximisation of a single asset, rather than those that require the balancing of multiple assets. Here, we built on a recent finding that medial OFC tracks the internal state given by cumulative satiety or wealth over a sequence of trials 23 , 24 . We reasoned that by encoding these signals, the OFC and interconnected areas of the medial prefrontal cortex might allow animals to compute ongoing levels of competing assets, and dynamically adjust choices to both replenish immediate needs and guard against future scarcity.…”
mentioning
confidence: 99%
“…Loss aversion has been subject to challenges in recent years from research that emphasizes context dependence. These studies have found consistent shifts in decisionmaking as a function of recent history (Jeuchems, Balaguer, Ruz, & Summerfield, 2017;Post, van den Assem, Baltussen, & Thaler, 2008;Rigoli et al, 2016) or current context (Louie, Khaw, & Glimcher, 2013;Yamada, Louie, Tymula, & Glimcher, 2018) explained by biologically plausible normalization models that consider values relative to their context.…”
Section: Challenges To Loss Aversionmentioning
confidence: 84%
“…The observation that vmPFC activity is sensitive to different reward types (e.g., money, food), across a variety of choice tasks, has led to the proposal that vmPFC represents a "common currency" of subjective value (Levy & Glimcher, 2012). Recent fMRI evidence suggests that vmPFC not only responds to momentary gains and losses, but also tracks cumulative reward histories (Juechems, Balaguer, Ruz, & Summerfield, 2017) that are accompanied by shifts in risk preference. Support for the idea that vmPFC plays a role in the construction of subjective utility has also come from lesion studies in which patients with focal vmPFC damage were compared to patients with damage to other brain regions, as well as to healthy controls.…”
Section: Value and The Vmpfcmentioning
confidence: 99%